ANALISA PROJECT LIFE CYCLE PEMBANGUNAN KAWASAN WISATA PUSAT KEBUDAYAAN BALI DI KLUNGKUNG - Nuriawan, I Nengah Alit (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2024)
The Bali Cultural Center (PKB) Tourist Area in Klungkung is the focus of analysis in this article, which traces each stage of project development from conception to implementation. The planning phase is emphasized as an important foundation, where the vision of sustainability and cultural sustainability is deeply understood and integrated. Community involvement is a key element in maintaining the sustainability of this project, with active participation in decision making and project implementation. Local economic empowerment programs and the promotion of cultural activities are important points in strengthening the relationship between development and cultural preservation. Tourism impact management is a significant challenge, and this project creates a new paradigm by combining sustainability and culture as the main foundation. Sustainability strategies in managing the number of tourists and environmental preservation are priorities in maintaining cultural authenticity and environmental sustainability. Project life cycle analysis highlights the importance of innovation and adaptation to the latest technology in advancing tourism destinations. Through lessons learned from this project, this article offers in-depth insight into the importance of sustainability and culture in the development of tourism destinations, not only in Bali, but also throughout the world.